Studies of kaonic atoms at the DAΦNE collider: from SIDDHARTA to SIDDHARTA-2. (April 2020) - Sirghi, Diana; Amirkhani, Aidin; Baniahmad, Ata; Bazzi, Massimiliano; Bosnar, Damir; Bragadireanu, Mario; Carminati, Marco; Cargnelli, Michael; Clozza, Alberto; Curceanu, Catalina; De Paolis, Luca; Del Grande, Raffaele; et al.
Abstract: The DAΦNE electron-positron collider of the Laboratori Nazionali di Frascati of INFN is a worldwide unique low-energy kaon source and for this reason is suitable for low-energy kaon physics like kaonic atoms and kaon-nucleons/nuclei interaction studies. Kaonic atoms are atomic systems where an electron is replaced by a negatively charged kaon, containing the strange quark, which interacts in the lowest orbits with the nucleus also by the strong interaction. As a result, their study offers the unique opportunity to perform experiments equivalent to scattering at vanishing relative energy. This allows to study the strong interaction between the antikaon and the nucleon or the nucleus "at threshold", without the need of ad hoc extrapolation to zero energy, as in scattering experiments. The most precise kaonic hydrogen measurement to date, together with an exploratory measurement of kaonic deuterium, were carried out by the SIDDHARTA collaboration at the DAΦNE electron-positron collider of LNF-INFN, by combining the excellent quality kaon beam delivered by the collider with new experimental techniques, as fast and precise Silicon-Drift X-ray Detectors. The measurement of kaonic deuterium will be realized in the near future by SIDDHARTA-2, a major upgrade of SIDDHARTA.